2016
DOI: 10.1016/s1875-5372(17)30064-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fe Nanoparticles via One-Step Reduction Method

Abstract: Fe nanoparticles were synthesized via a novel one-step reduction method. The excessive citric acid helps to obtain pure and high crystallinity α-Fe at the appropriate temperature (620 o C). The Fe nanoparticles were characterized by the X-ray diffraction, transmission electron microscopy (TEM) and vibrating sample magnetometer (VSM). The morphological characterization indicates that the Fe nanoparticles present spherical shape with diameter of 30 nm. The magnetization hysteresis loops reveal the high saturatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…[38] 198.97 Am 2 /kg. [39] Harshiny Muthukumar et al synthesized bio and chemically-derived FeO nanoparticles, which possess ferromagnetic properties at room temperature with a coercivity value of 94.7 Oe for chemically-derived FeO and 92.12 Oe for bio-derived FeO nanoparticles which are lower values than that of our work. [40] N. Mohamed Basith et al synthesized Fe 3 O 4 via the sol-gel approach that reveals ferromagnetic behavior at room temperature with a coercivity value of 13.63 Oe, which is much lower than that of our samples.…”
Section: Vsm Analysiscontrasting
confidence: 71%
See 1 more Smart Citation
“…[38] 198.97 Am 2 /kg. [39] Harshiny Muthukumar et al synthesized bio and chemically-derived FeO nanoparticles, which possess ferromagnetic properties at room temperature with a coercivity value of 94.7 Oe for chemically-derived FeO and 92.12 Oe for bio-derived FeO nanoparticles which are lower values than that of our work. [40] N. Mohamed Basith et al synthesized Fe 3 O 4 via the sol-gel approach that reveals ferromagnetic behavior at room temperature with a coercivity value of 13.63 Oe, which is much lower than that of our samples.…”
Section: Vsm Analysiscontrasting
confidence: 71%
“…Hu Ping et al. prepared sol‐gel mediated Fe nanoparticles which show ferromagnetic behavior with a magnetic saturation (M s ) of 198.97 Am 2 /kg [39] . Harshiny Muthukumar et al.…”
Section: Resultsmentioning
confidence: 99%
“…Although the fabrication of a magnetic iron nanostructure is quite difficult, much effort has been made to prepare Fe nanostructures using ball milling, DC arc plasma and sputtering methods. 27 Among these, Fe nanostructures such as nanoflakes, nanoparticles and core–shell (Fe as core coated with oxide shell) structures are evidently the more common structures, because oxide shells not only prevent Fe from oxidation in the presence of air, but also prevent the forefront reflections as previously observed in pure Fe sheets that show negligible microwave absorption, due to the good conductivity of Fe elements ( σ ∼ 10 7 S cm −1 ) and the strong skin effect at GHz high frequency. This is the main reason that Fe structures have been part of rather few studies.…”
Section: Materials Used For Emi Shieldingmentioning
confidence: 99%
“…At rst, Fe nanoparticles (FeNPs) were synthesized as described previously. 19 Zn nanoparticles (ZnNPs) were prepared through the precipitation method as described by Kumar et al 20 In addition, the simple one-step reduction method for the synthesis of Cu nanoparticles (CuNPs) was explained in our previous report, 17 whereas nano Se was prepared according to the method described by Khan et al 18 The formulation and approximate composition of the nano-nutrient diet are shown in Table 1.…”
Section: Preparation Of the Hybrid Nano-nutrient Dietmentioning
confidence: 99%